2006
DOI: 10.1016/j.autrev.2005.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Liver stem cell-derived β-cell surrogates for treatment of type 1 diabetes

Abstract: Consistent with the common embryonic origin of liver and pancreas as well the similar glucosesensing systems in hepatocytes and pancreatic β-cells, it should not be surprising that liver stem cells/hepatocytes can transdifferentiate into insulin-producing cells under high-glucose culture conditions or by genetic reprogramming. Persistent expression of the pancreatic duodenal homeobox-1 (Pdx1) transcription factor or its super-active form Pdx1-VP16 fusion protein in hepatic cells reprograms these cells into pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 28 publications
0
19
0
2
Order By: Relevance
“…Pdx1 is widely regarded as a master transcriptional regulator of the pancreas and is critical for development (11)(12)(13), regeneration (10,14), and maintenance of ␤-cell function (14,15). Liver stem cells (16) and adult hepatocytes (17,18) reportedly have been reprogrammed by ectopic overexpression of PDX1 into IPCs that are also capable of restoring euglycemia in diabetic mice. However, the strategies involving the use of viruses as a means for gene delivery in these studies raise safety concerns.…”
mentioning
confidence: 99%
“…Pdx1 is widely regarded as a master transcriptional regulator of the pancreas and is critical for development (11)(12)(13), regeneration (10,14), and maintenance of ␤-cell function (14,15). Liver stem cells (16) and adult hepatocytes (17,18) reportedly have been reprogrammed by ectopic overexpression of PDX1 into IPCs that are also capable of restoring euglycemia in diabetic mice. However, the strategies involving the use of viruses as a means for gene delivery in these studies raise safety concerns.…”
mentioning
confidence: 99%
“…More importantly, these insulin-secreting liver tissues corrected STZ-induced hyperglycemia to maintain normal blood glucose levels for a period of 8 months [37,38]. However, Yang [39] found that, in some cases, PDX1-reprogrammed liver tissue is only capable of forming pancreatic  progenitor cells that only further differentiate into functional IPCs under a state of high glucose in vitro or in vivo. To date, no evidence has been found which shows that the modified liver cells proliferate in vitro and can reach a sufficient number of functional cells for transplantation therapy.…”
Section: Hepatic Stem Cellsmentioning
confidence: 99%
“…Pdx-1 is a transcription factor expressed in all progenitor cells that eventually become exocrine and endocrine pancreas. No pancreas tissue develops in Pdx-1-deficient mice, however the expression of Pdx-1 in hepatocytes does not result in the formation of a functional endocrine pancreas, suggesting that the Pdx-1 transcription factor is necessary but not sufficient to induce the differentiation into pancreatic tissue [64]. Nonetheless, Zalzman et al [66] reported that the transplantation of these virally transfected cells were transplanted under the kidney capsule of STZ induced diabetic NOD-scid mice resulted in the restoration of normoglycemia for greater than 80 days.…”
Section: Liver Stem Cellsmentioning
confidence: 99%
“…The plasticity of liver stem cells is well known [63]. Through manipulation with transcription factors, hepatic stem cells have been shown to differentiate into insulinproducing cells [64]. Yang et al [65] derived islet-like clusters capable of secreting insulin in vitro in a glucose sensitive manner from rat hepatic oval cells, which are considered to be hepatic stem cells.…”
Section: Liver Stem Cellsmentioning
confidence: 99%